Loyalty - Smith, Lionel (McGill Law Journal, 2020)
Loyalty has many meanings, within and without the law. There is a difficult question about whether loyalty is a virtue, inasmuch as one can be loyal to many causes, not all of them virtuous. For many jurists, the notion of loyalty evokes the common law’s fiduciary relationship and the norms that are particular to that … Continued